Manipulating Orbital Angular Momentum Entanglement in Three-Dimensional Spiral Nonlinear Photonic Crystals - Qian Yu; Chuan Xu; Sixin Chen; Pengcheng Chen; Saiwei Nie; Shijie Ke; Dunzhao Wei; Min Xiao; Yong Zhang (Photonics, 2022)
We propose and theoretically investigate two-photon orbital angular momentum (OAM) correlation through spontaneous parameter down-conversion (SPDC) processes in three-dimensional (3D) spiral nonlinear photonic crystals (NPCs). By properly designing the NPC structure, one can feasibly modulate the OAM-correlated photon pair, which provides a potential platform to realize high-dimensional entanglement for quantum information processing and quantum communications.